The construction of winter wheat smart water saving irrigation system based on big data and internet of things. (2017) - Zhang, Peng; Zhang, Qian; Liu, Fusheng; Cao, Ning; Song, Changqing; Li, Junqing; Liu, Yanmin; Yang, Cuinan; Higgs, Russell; O'Hare, Gregory M.P.; Xu, Lina
The advent of emerging big data and internet of things, a large number of agriculture data such as the seeding condition, soil moisture, fertiliser, water, pests and meteorology, which could be effectively analysed to guide the smart agriculture. In this paper, the winter wheat smart water saving irrigation system is established based on technologies including big data and internet of things. Through the automatic monitor system of winter wheat growing environment, the big data centre intelligently stores, screens, calibrates, mines and extracts the monitoring data, a system of winter wheat irrigation and fertilisation decision-making based on big data was built. According to the testing data and the weather forecast data, this system can forecast the water requirement of winter wheat in different growth periods and make decisions on automatic irrigation and fertilisation, leading to the timely and proper irrigation of crops.